1989
DOI: 10.1007/bf01907002
|View full text |Cite
|
Sign up to set email alerts
|

Coronary collateral reserve during exercise induced ischemia in swine

Abstract: We determined coronary collateral vasodilator reserve during exercise-induced ischemia in 17 mini-swine. We induced coronary collateral development in the left circumflex bed by placing an ameroid occluder on that artery. Four weeks later we studied the animals at rest and during exercise (EX) eliciting heart rates (HR) of 240 and 265 beats/min. We measured myocardial blood flow with microspheres and myocardial function by wall thickness sonomicrometry gauges. At matched exercise HRs we treated the animals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…The coronary artery system closely resembles the human situation, as does the ratio of heart weight to body weight [18,40]. However, existing collaterals in pig hearts are always open and no additional collaterals can be recruited during an ischemic episode [18,39]. That is why cardiac ischemia is poorly tolerated by pigs and relatively short ischemic periods often lead to fatal arrhythmias and rapid development of necrosis [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coronary artery system closely resembles the human situation, as does the ratio of heart weight to body weight [18,40]. However, existing collaterals in pig hearts are always open and no additional collaterals can be recruited during an ischemic episode [18,39]. That is why cardiac ischemia is poorly tolerated by pigs and relatively short ischemic periods often lead to fatal arrhythmias and rapid development of necrosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Although pigs are extremely susceptible to preoperative stress and therefore require efficient premedication to reduce the risk of arrhythmia [39], pig hearts have several properties that are of particular interest for the study of myocardial ischemia or infarction. The coronary artery system closely resembles the human situation, as does the ratio of heart weight to body weight [18,40]. However, existing collaterals in pig hearts are always open and no additional collaterals can be recruited during an ischemic episode [18,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, exercise training enhances collateral development and regional myocardial perfusion in the porcine model of chronic coronary occlusion. 2,3,25,26 Furthermore, exercise training has been shown to improve myocardial function in patients with ischemic cardiomyopathy 27 and to stimulate blood flow to the myocardium via native and developing collaterals. 3 Therefore, exercise training may act as a nonpharmacological therapeutic strategy 20,21 to enhance collateral development and/or stimulate cellular pathways (ie, flow-and shear stress-dependent signaling mechanisms) involved in ecNOS regulation and induce beneficial adaptations of collateral-dependent microvascular endothelium.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…Using this technique, O'Konski et al (16) demonstrated that after 3-4 wk of gradual coronary artery occlusion, pigs develop a significant increase in coronary collateral blood flow to the compromised area reaching almost same level as the flow in the normal area at rest. However, the territory supplied by the ameroid-constricted artery is clearly ischemic during exercise or pharmacological vasodilation (17). The nature of this limitation remains unclear and it has been variously ascribed to new collaterals possessing less smooth muscle than normal arterioles (12), having impaired function (18) or simply to an insufficient number of collaterals forming in the ischemic territory.…”
Section: Introductionmentioning
confidence: 99%